Factors influencing the environmental sustainability and growth of hydrotreated vegetable oil (HVO) in Sweden. (September 2019) - Soam, Shveta; Hillman, Karl
Abstract: The study analyzes the factors influencing the environmental sustainability and growth of hydrotreated vegetable oil (HVO) in Sweden. The major feedstocks identified in the HVO supply chain are palm oil, rapeseed oil, PFAD, tallow and tall oil. LCA studies reveal that feedstock grown on-purpose have larger life cycle GHG emissions than residual feedstock. However, due to the limited supply of residual feedstock there is a need to be more dependent on domestic sustainable resources. The complexity of feedstock, origin, processing technologies, allocation approach, land use changes (LUC) and selection of environmental categories could result in variations of the LCA results. To achieve national emissions target, policy instruments such as reduction obligations and tax incentives favor the market for HVO. However, to see more comprehensive results of the HVO development, research is needed to integrate the technological perspective from pilot scale to the commercialized market at local, regional and global level. Graphical abstract: Unlabelled Image Highlights: Environmental impact of residual feedstock lower than on-purpose feedstock PFAD, the largest feedstock used for HVO production Choice of allocation, processing methods and by-products use crucial factors in LCA Policy and regulations have a direct influence on HVO growth. Mixed pool of local feedstocks required to meet the high demand of HVO